Protective Effects of Myricetin on Benzo[a]pyrene-Induced 8-Hydroxy-2'-Deoxyguanosine and BPDE-DNA Adduct - Seung-Cheol Jee; Min Kim; Kyeong Seok Kim; Hyung-Sik Kim; Jung-Suk Sung (MDPI AG, 2020)
Benzo[a]pyrene (B[a]P), a group 1 carcinogen, induces mutagenic DNA adducts. Myricetin is present in many natural foods with diverse biological activities, such as anti-oxidative and anti-cancer activities. The aim of this study was to investigate the protective effects of myricetin against B[a]P-induced toxicity. Treatment of B[a]P induced cytotoxicity on HepG2 cells, whereas co-treatment of myricetin with B[a]P reduced the formation of the B[a]P-7,8-dihydrodiol-9,10-epoxide (BPDE)-DNA adduct, which recovered cell viability. Furthermore, we found a protective effect of myricetin against B[a]P-induced genotoxicity in rats, via myricetin-induced inhibition of 8-hydroxy-2'-deoxyguanosine (8-OHdG) and BPDE-DNA adduct formation in the liver, kidney, colon, and stomach tissue. This inhibition was more prominent in the liver than in other tissues. Correspondingly, myricetin regulated the phase I and II enzymes that inhibit B[a]P metabolism and B[a]P metabolites conjugated with DNA by reducing and inducing CYP1A1 and glutathione S-transferase (GST) expression, respectively. Taken together, this showed that myricetin attenuated B[a]P-induced genotoxicity via regulation of phase I and II enzymes. Our results suggest that myricetin is anti-genotoxic, and prevents oxidative DNA damage and BPDE-DNA adduct formation via regulation of phase I and II enzymes.